ETNOBOTANI MASYARAKAT DAYAK SURU’ STUDI KASUS DUSUN SUNGAI TEKUYUNG DESA TANGAI JAYA KECAMATAN MENTEBAH KABUPATEN KAPUAS HULU - Joni, Alfius; Oramahi, H. A.; Ardian, Hafiz (Universitas Tanjungpura, 2015)
This study aims to identify and expand the use of herbs used by the Dayak Suru’ community in Dusun sungai Tekuyung Tangai jaya village, District Mentebah Kapuas Hulu and to know the parts of plants that are used and the plants benefit to society. The study was conducted in three stages, namely literature review, observation and data processing. Research on Dayak community Suru' at dusun Sungai Tekuyung Tangai jaya village, District Mentebah get as many as 95 species of 46 families And are divided into nine groups of uses, medicinal plants (24 species ), dye plants (1 species), food crops Livestock ( three species ), ornamental plants (6 species), producers of plant crafts (4 species ), plant pesticide plant (1 species ), plant manufacturers firewood (5 species) and plant manufacturers of building materials ( 11 species ). Many families used in family Arecaceae, Dipterocarpaceae, Solanaceae and Poaceae. Many plant species are used in nine groups usability. Ciko (Kaempferia galanga L), Taro (Caladium sp), Banana (Musa acuminata), Paddy (Oryza sativa), Selasih (Fasiforia foetida L), Kangkung (Ipomoea aquatica Forsk) dan Serai (Cymbopogon citratus). Keywords: Dayak Suru'; Ethnobotany; River Tekuyung